Socio-economics of trawl fisheries in Southeast Asia and Papua New Guinea : Proceedings of the Regional Workshop on Trawl Fisheries Socio-economics 26–27 October 2015 Da Nang, Viet Nam and Socio-economic Write-shop 25–26 April 2016 Cha Am, Thailand - (:unkn) unknown (Food and Agriculture Organization of the United Nations, FAO, 2017)
Socio-economic surveys were carried out in pilot sites in Papua New Guinea (Gulf of Papua Prawn Fishery), the Philippines (Samar Sea), Thailand (Trat and Chumphon) and Viet Nam (Kien Giang) as part of the Strategies for Trawl Fisheries Bycatch Management Project (REBYC-II CTI), funded by the Global Environment Facility (GEF) and executed by FAO. No study was conducted in Indonesia as a result of the ban on trawl fisheries which began in January 2015. However, a paper based on key informant interviews was prepared. The socio-economic studies were undertaken to understand the contribution of trawl fisheries to food security and livelihoods, and determine the potential impacts of management measures on stakeholder groups. The socio-economic information collected included: the demographic structure of vessel owners and crew; fishing practices (boat, gear, season, duration; catch composition, value chain and markets); contribution to livelihoods, food security and nutrition; role of women; costs and income from trawling; catch/income sharing arrangements; links with other sectors; and perceptions (resources, participation, compliance and the future). A common finding from the surveys in Papua New Guinea, the Philippines and Thailand was the low level of education among fishers. In the Philippines, Thailand and Viet Nam, trawl fisheries are very important for livelihoods, and many fishers depend solely on fishing. The important findings in Papua New Guinea included: (a) the absence of direct benefit from trawl fisheries to resource owners or to the provinces; (b) bycatch utilization is very low because of a lack of accessibility to trawlers for communities, leading to the discarding of bycatch; (c) weak implementation of management rules by provincial fisheries officers as a result of limited capacity; and (d) provincial and national fisheries management plans do not address women’s issues. In the Philippines, the important findings included: (a) differences of perception between municipal and commercial trawl fishers with respect to the condition of fishery resources; (b) use of income from fishing on children’s education and basic needs; (c) willingness of municipal trawl fishers—but not commercial trawl fishers—to shift to other gears; (d) the preference for gillnets should all trawl fishers be required to shift to other gears; (e) catch from trawling contributes to fish for home consumption; and (f) the fishing operations of small- and medium-scale fishing boats are still profitable. The survey in the pilot site in Thailand showed that the number of fishing boats is still increasing, in spite of the decrease in the number of fishing households. There is a low level of knowledge and awareness of fisheries regulations. Management measures, when enforced, would have a huge impact on livelihoods because many fishers rely solely on fishing for their livelihoods. When considering which management options to implement, the similarities and differences in perceptions among fishers should be taken into account. In Viet Nam, there is a very close connection between trawl fisheries and aquaculture because trawl fisheries provide the raw materials necessary to the fishmeal industry. There is an increasing demand for raw materials for fishmeal. Fishers practically land and utilize all catch. Low-value fish account for 30–40 percent of trawlers’ landing volume. There is a significant loss in quality during the capture stage as a result of the long towing time (7–8 hours per haul) as well as significant post-harvest losses (20–30 percent). In Indonesia, the implementation of the moratorium for foreign vessels and the new trawling ban enforced in 2015 has made it difficult for many crew members and fish workers to find another job. Companies cannot operate their processing facility at full capacity and find it difficult to maintain trade with buyers abroad. On the other hand, the ban apparently has provided an opportunity for small-scale fishers to supply shrimp to the processing industry in Arafura region.